2022
DOI: 10.1186/s12872-022-02726-2
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced Piezo1 activation promote mitochondrial-dependent apoptosis in vascular smooth muscle cells

Abstract: Objective Mechanical damage plays an essential role in the progression of atherosclerosis. Piezo1 is a new mechanically sensitive ion channel. The present study investigated the vascular smooth muscle cells (VSMCs) apoptosis induced by Piezo1 activation and explored its underlying mechanism. Methods We evaluated cell viability and apoptosis rate with cell counting kit-8 (CCK-8) and Annexin V-FITC/PI flow cytometry assay, respectively. And then West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…[46] VSMC Piezo1 was further linked to increased contraction and proliferation [17,47] and apoptosis. [48] Additionally, Piezo1 was upregulated in abdominal aortic aneurysms downstream of netrin-1. [49] Although the Piezo channels are generally targeted to the plasma membrane, [50,51] where they are localized in a curvature dependent way, [52] localization to diverse intracellular membranous organelles, including sarcoplasmic and endoplasmic reticulum, mitochondria, Golgi has been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…[46] VSMC Piezo1 was further linked to increased contraction and proliferation [17,47] and apoptosis. [48] Additionally, Piezo1 was upregulated in abdominal aortic aneurysms downstream of netrin-1. [49] Although the Piezo channels are generally targeted to the plasma membrane, [50,51] where they are localized in a curvature dependent way, [52] localization to diverse intracellular membranous organelles, including sarcoplasmic and endoplasmic reticulum, mitochondria, Golgi has been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we identify piezo1 as a driver of ECM rigidity induced VSMC hypertrophy. VSMC piezo1 expression is upregulated in mouse models of atherosclerosis and abdominal aortic aneurysms, with dysregulation of VSMC mechanosensation shown to drive these disease states (Qian et al, 2022;Yin et al, 2022). Furthermore, reduced aortic compliance is observed in both atherosclerosis and abdominal aortic aneurysms (Glasser et al, 1997;Mitchell et al, 2010;Lacolley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The above data shows that VSMC hypertrophy on rigid substrates is mediated by SAC activation. Piezo1 is a SAC known to be involved in atherosclerosis and abdominal aortic aneurysm mediated VSMC dysfunction (Qian et al, 2022;Yin et al, 2022). Whether piezo1 is involved in VSMC hypertrophy remains unknown.…”
Section: Piezo1-mediated Calcium Influx Destabilises Microtubules And...mentioning
confidence: 99%
See 1 more Smart Citation
“…VSMC mechanosensation depends on the swift opening of Piezo1, a tension-gated ion channel that allows the influx of calcium (Ca 2+ ) ions upon activation to regulate the vascular development, blood pressure, and hypertension-dependent arterial remodeling [18][19][20][21]. Recent studies identified Piezo1 as the culprit for VSMC maladaptive mechanosensation in aortic aneurysm, a lethal vascular disease that affects almost exclusively the aged population [22].…”
Section: Introductionmentioning
confidence: 99%